2017
DOI: 10.5344/ajev.2016.15114
|View full text |Cite
|
Sign up to set email alerts
|

Population Diversity of Grape Phylloxera in California and Evidence for Sexual Reproduction

Abstract: Until recently, the foliar forms of grape phylloxera have been absent or very rare in California, and nodosities have not been common on resistant rootstocks. Foliar phylloxera are now widely spread in the mothervine plantings of grape rootstock nurseries in Yolo and Solano counties. Nodosities on resistant rootstocks have also been frequently observed. To determine the genetic relationships within and among these seemingly new types of phylloxera, collections were made across California from 2009 to 2011. Fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
1
11
0
1
Order By: Relevance
“…As previously found in other regions (Vorwerk and Forneck , , Islam et al , Forneck et al , Riaz et al ), the parthenogenetic nature of the insect in Argentina is confirmed by P sex values, the excess of heterozygous individuals and the significant deviations from the Hardy–Weinberg equilibrium. The possible occurrence, however, of sporadic sexual reproduction cannot be discarded.…”
Section: Discussionsupporting
confidence: 79%
“…As previously found in other regions (Vorwerk and Forneck , , Islam et al , Forneck et al , Riaz et al ), the parthenogenetic nature of the insect in Argentina is confirmed by P sex values, the excess of heterozygous individuals and the significant deviations from the Hardy–Weinberg equilibrium. The possible occurrence, however, of sporadic sexual reproduction cannot be discarded.…”
Section: Discussionsupporting
confidence: 79%
“…The likely patterns of the introductions of phylloxera into worldwide viticulture regions from its native habitat have Table 2 Genetic diversity parameters for grape phylloxera populations obtained in 9 Swiss (CH) and German (DE) regions been extensively analyzed by different authors using diverse genetic markers, including mitochondrial (Downie 2002) and nuclear polymorphisms (Forneck et al 2000;Lund et al 2017;Riaz et al 2017). Whereas phylloxera populations from Vitis species like V. vulpina and V. arizonica are suggested to be the more likely source of introductions into viticulture regions like California (USA), South Africa, Australia, New Zealand and South America (Arancibia et al 2018;Downie 2002;Lund et al 2017), there is a general agreement that all European phylloxera introductions are likely to come from northeastern American populations, where V. riparia dominates (Downie 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A set of seven highly polymorphic SSR markers (Phy_III_55, Phy_III_30, Phy_III_36, Dvit6, DV4, DV8 and DVSSR4 (Forneck et al 2017a)) were selected and analyzed in the 335 phylloxera samples. Polymerase chain reaction (PCR), separation of fragments and allele calling was performed following the procedures detailed in Riaz et al (2017) and Forneck et al (2017a).…”
Section: European Grape Phylloxera Genotypingmentioning
confidence: 99%
“…Foliar phylloxera has been rare in California, until the discovery of a widespread outbreak of leaf-galling phylloxera that occurred in grape rootstock nursery plantings in Yolo and Solano counties. One hundred and twenty-two of the 170 leaf-galling phylloxera samples tested in a previous study [ 32 ] were determined to be the same clone, represented in this study by the WEO4802 sample; the remaining samples were closely related. STRUCTURE analysis determined that the WEO4802 sample was a mixture of the V .…”
Section: Discussionmentioning
confidence: 99%